Experimental Study on Deformation Behavior and Integrity Failure of Cement Sheath in Underground Gas Storage - Liang, Yinlong; Hou, Yongjun; Han, Yutian (International Journal of Natural Resources and Environmental Studies, 2026)
The cyclic injection-production operations in underground gas storage (UGS) pose significant challenges to the sealing integrity of wellbore cement sheath under cyclic loading. To elucidate the failure mechanism, this study systematically investigates the deformation behavior and integrity of cement sheath used in UGS through mechanical experiments. Firstly, uniaxial, ambient-temperature triaxial, high-temperature triaxial, and cyclic loading-unloading tests were conducted on set cement to clarify the evolution laws of its mechanical properties. The results indicate that set cement exhibits brittle failure under uniaxial compression. The confining pressure in triaxial tests significantly enhances its strength and ductility, while a high-temperature environment induces a pronounced thermal softening effect, leading to earlier yielding and enhanced plastic deformation. Under cyclic loading, the cement displays a hysteresis loop, with plastic strain accumulating continuously. Furthermore, the upper limit of cyclic stress is identified as the key factor governing its fatigue damage. Based on these findings, engineering application guidance is proposed, focusing on the selection of high-temperature resistant materials and the control of operational pressure. This provides a theoretical basis for ensuring the long-term safe operation of UGS wells.